2013
DOI: 10.1182/blood.v122.21.559.559
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Of Two Combination Iron Chelation Regimens, Deferiprone and Deferasirox Versus Deferiprone and Deferoxamine, In Pediatric Patients With β-Thalassemia Major

Abstract: Background Patients with severe iron overload may require a more rapid and efficient therapy for reduction in iron burden than what can be provided with chelation monotherapy. Combined chelation using deferoxamine (DFO) and deferiprone (DFP) is widely used to treat such patients, but the inconvenience of parenteral administration of DFO reduces the effectiveness of this regimen in many patients. Minimal data are available on the safety and efficacy of combined two orally active chelator agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…Combination of the orally active DFX with DFO has also had some clinical evaluation (Lal et al , ) and is the subject of further prospective trials (Aydinok et al , ). The combination of two orally active chelators, DFP with DFX, would be more appealing to patients than therapies involving parenterally administered DFO but clinical experience is limited (Elalfy et al , ).…”
mentioning
confidence: 99%
“…Combination of the orally active DFX with DFO has also had some clinical evaluation (Lal et al , ) and is the subject of further prospective trials (Aydinok et al , ). The combination of two orally active chelators, DFP with DFX, would be more appealing to patients than therapies involving parenterally administered DFO but clinical experience is limited (Elalfy et al , ).…”
mentioning
confidence: 99%
“…Small studies have explored the combination of DFX and DFO or DFP, showing a rapid reduction in systemic and myocardial iron and the potential of a synergistic or additive effect on iron removal (Farmaki et al , ; Lal et al , ). Recent preliminary data from a prospective randomized 1‐year study suggested SF, cardiac T2*, compliance and quality of life were improved in children with TM who received DFP and DFX compared to those who received DFP and DFO (El‐Alfy et al , ). The first results from a large prospective study show that combined therapy of DFX and DFO resulted in an improvement in cardiac T2* during 12 months of treatment with a considerable decrease in LIC in patients with transfusional severe cardiac and liver iron (Aydinok et al , ).…”
Section: Managing Iron Chelation In Children With Transfusion‐dependementioning
confidence: 99%
“…Ten were multicentre trials (Calvaruso 2015; Elalfy 2015; Galanello 2006; Maggio 2009; Olivieri 1997; Pennell 2006; Pennell 2014; Taher 2017; Tanner 2007; Vichinsky 2007) and ranged from two centres in one country (Calvaruso 2015; Elalfy 2015; Olivieri 1997) to 44 centres in multiple countries (Vichinsky 2007). Six were single-centre trials (Aydinok 2007; Bahnasawy 2017; Badawy 2010; El Beshlawy 2008; Hassan 2016, Mourad 2003).…”
Section: Resultsmentioning
confidence: 99%
“…The number of participants enrolled in the trials ranged from 24 (Aydinok 2007) to 213 (Maggio 2009). Sample-size calculations were reported in eight trials (Calvaruso 2015; Elalfy 2015; El Beshlawy 2008; Maggio 2009; Pennell 2006; Pennell 2014; Tanner 2007; Vichinsky 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation